2014
DOI: 10.1159/000366232
|View full text |Cite
|
Sign up to set email alerts
|

Early Effects of Dexamethasone Implant on Macular Morphology and Visual Function in Patients with Macular Edema Secondary to Retinal Vein Occlusion

Abstract: Purpose: To evaluate the early effects of the intravitreal erodible dexamethasone implant Ozurdex in patients with macular edema due to retinal vein occlusion (RVO). Methods: Eyes with macular edema due to RVO were prospectively included in the study and received a 700-μg dexamethasone implant. Best-corrected visual acuity (BCVA) measurement, complete ophthalmic evaluation and spectral-domain optical coherence tomography were performed at baseline and 1, 2, 3, 7, 14, 21, 28, 60, and 90 days after treatment. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Studies have shown clinically significant improvement and increased vision after the administration of the IDI injection in patients with RVO. [ 9 10 14 15 ] In the present study, the IDI injection decreased CFT value and increased BCVA value in both the BRVO and CRVO groups. Moreover, a significant difference was observed between pre- and post-injection CFT and BCVA values ( P < 0.001 and P < 0.001, respectively).…”
Section: Discussionsupporting
confidence: 53%
“…Studies have shown clinically significant improvement and increased vision after the administration of the IDI injection in patients with RVO. [ 9 10 14 15 ] In the present study, the IDI injection decreased CFT value and increased BCVA value in both the BRVO and CRVO groups. Moreover, a significant difference was observed between pre- and post-injection CFT and BCVA values ( P < 0.001 and P < 0.001, respectively).…”
Section: Discussionsupporting
confidence: 53%
“…Our findings of a significant reduction in CMT after 3 h support the hypothesis that intravitreal long-release steroids play a role in humans, inducing a rapid response in terms of reduction of CMT. Veritti investigated the effect of dexamethasone implants on macular morphology and visual function in eyes with RVO [25] and DME [26]. In both pathologies, a fast reduction in macular thickness was seen, starting 1 day after the administration of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Also, some studies whose final outcome was not BCVA and CRT, the results were not reported, and patients had already received other treatments were also excluded. Finally, seven eligible studies including 393 eyes were used in the present meta-analysis [7][8][9][10][11][12]. The flow chart for the study selection process is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%